Opening the GATE: systems thinking from the global assistive technology alliance. (3rd July 2020) - Layton, Natasha; Bell, Diane; Buning, Mary Ellen; Chen, Shih-Ching; Contepomi, Silvana; Delgado Ramos, Vinicius; Hoogerwerf, Evert-Jan; Inoue, Takenobu; Moon, Inhyuk; Seymour, Nicky; Smith, Roger O.; de Witte, Luc
Abstract: Purpose: This paper describes international actions to collaborate in the assistive technology (AT) arena and provides an update of programmes supporting AT globally. Methods: The World Health Organisation (WHO) identifies the severe global uneven distribution of resources, expertise and extensive unmet need for AT, as well the optimistic substantial capability for innovations and developments in appropriate and sustainable AT design, development and delivery. Systems thinking and market shaping are identified as means to address these challenges and leverage the ingenuity and expertise of AT stakeholders. Results: This paper is a 'call to action', showcasing emerging AT networks as exemplars of a distributed, but integrated mechanism for addressing AT needs globally, and describing the Global Alliance of Assistive Technology Organisations (GAATO) as a vehicle to facilitate this global networking. Conclusion: Partners in this Global Alliance aim to advance the field of assistive technology by promoting shared research, policy advocacy, educating people and organisations within and outside the field, teaching, training and knowledge transfer by pulling together broad-based membership organisations. Implications for Rehabilitation: Collegial, cross discipline and multi-stakeholder collaborations support assistive technology research and practice. Knowledge exchange within and across countries and regions is mutually beneficial. Self-organising assistive technology communities are emerging and supported by global movements such as WHO GATE and GAATO.